2015
DOI: 10.1093/glycob/cwv046
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface glycan engineering of neural stem cells augments neurotropism and improves recovery in a murine model of multiple sclerosis

Abstract: Neural stem cell (NSC)-based therapies offer potential for neural repair in central nervous system (CNS) inflammatory and degenerative disorders. Typically, these conditions present with multifocal CNS lesions making it impractical to inject NSCs locally, thus mandating optimization of vascular delivery of the cells to involved sites. Here, we analyzed NSCs for expression of molecular effectors of cell migration and found that these cells are natively devoid of E-selectin ligands. Using glycosyltransferase-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…13 These results also elicit the question of whether the appropriate glycosyltransferases/glycosidases and/or appropriate substrates for these enzymes are differentially expressed in these subpopulations of HSPCs. Such an understanding of this valuable population of cells will allow researchers to harness technologies 34,[54][55][56][57] that improve the migration capacity of these cells with the ultimate goal of using these cells in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…13 These results also elicit the question of whether the appropriate glycosyltransferases/glycosidases and/or appropriate substrates for these enzymes are differentially expressed in these subpopulations of HSPCs. Such an understanding of this valuable population of cells will allow researchers to harness technologies 34,[54][55][56][57] that improve the migration capacity of these cells with the ultimate goal of using these cells in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate through several examples the quantitative nature of our SPR-based IP approach, including the ability to 1) capture residual and transient interactions, 2) directly characterize the contribution of different post-translational modifications on ligands (that contribute particular isoforms of proteins) to the unique antigenic efficiencies of the antibody used for IP, and 3) determine binding constants of antibody-isolated ligands with the adhesion molecule of interest, E-selectin. This assay enabled a comparative and comprehensive binding analysis of CD44/hematopoietic cell E-/L-selectin ligand (HCELL) and P-selectin glycoprotein ligand-1 (PSGL-1) (11)(12)(13)(14)(15)53) in their native forms from KG1a cells with E-selectin. In addition, we include a comprehensive analysis of CD44/HCELL binding with E-selectin of two additional leukemic cell lines, THP-1 and HL-60.…”
mentioning
confidence: 99%
“…Several studies have shown that stem-cell tumor-tropism occurs along a chemotactic gradient, and several soluble factor receptors have been identified that influence stem-cell migration in a tumor model [26–30]. Additionally, there is evidence that the stem-cell interactions with astrocytes, neurons, and the extracellular matrix (ECM) could affect stem-cell migration following IND [31–34]. Although this review does not intend to cover the complexity of all migratory mechanisms utilized by stem cells in the brain, we highlight several of them in the section below.…”
Section: Molecular Mechanisms Of Stem-cell Migrationmentioning
confidence: 99%
“…Stem cells interact with vascular endothelial cells as they travel through circulation, with a loose adhesion to selectins and glycoproteins resembling that of disseminated lymphocytes [31]. Furthermore, like other tissue-homing cells, stem cells rely on interactions between cellular adhesion molecules to arrest on the surface of endothelial cells.…”
Section: Molecular Mechanisms Of Stem-cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation